2012
DOI: 10.1039/c2nr30823a
|View full text |Cite
|
Sign up to set email alerts
|

Band gap opening in methane intercalated graphene

Abstract: Recent experimental work has demonstrated production of quasi-free-standing graphene by methane intercalation. The intercalation weakens the coupling of adjacent graphene layers and yields Dirac fermion behaviour of monolayer graphene. We have investigated the electronic characteristics of a methane intercepted graphene bilayer under a perpendicularly applied electric field. Evolution of the band structure of intercalated graphene as a function of the bias is studied by means of density-functional theory inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Specifically, for graphite, local-density approximation overestimates the binding between the graphene layers, while GGA is very weak in binding. 37,38 Inclusion of the dispersion correction yields the correct layer distance of 3.719 Å, which is in good agreement with experiments. 37 …”
Section: Computational Detailssupporting
confidence: 83%
See 1 more Smart Citation
“…Specifically, for graphite, local-density approximation overestimates the binding between the graphene layers, while GGA is very weak in binding. 37,38 Inclusion of the dispersion correction yields the correct layer distance of 3.719 Å, which is in good agreement with experiments. 37 …”
Section: Computational Detailssupporting
confidence: 83%
“…26 The effect of doping can be readily clarified by the shift of the Dirac point in the band structure. 38 As seen from Figure 2, the Dirac point is located at the Fermi level in pristine graphene as well as in the cis -DR1P/graphene hybrid, whereas the corresponding Dirac point is shifted upward from the Fermi level in the trans -DR1P/graphene hybrid. The bands associated with the two DR1P isomers are characterized as flat bands, in contrast with the dispersed bands of graphene.…”
Section: Resultsmentioning
confidence: 86%
“…This reduced coupling, mediated through hopping between C-p and intercalant orbitals, in principle determines the critical (maximum) interlayer condensate transport in the BiSFET. We also note that band structure obtained for methane-intercalated bilayer graphene 35 for both AA and AB stacking turn out to be very similar. Our results for AA stacking can thus be qualitatively extended to intercalated AB stacked graphene, probably due to indirect interaction between the C layers.…”
Section: Electronic Structuresupporting
confidence: 51%
“…It has been shown that pure AAstacked BLG has multiple linear dispersion bands. The linear dispersion bands are mainly due to the electronic interlayer coupling that is suppressed by the Pauli repulsion between the graphene layers [32]. The first observation of our results is that linear dispersion around the K-point is not seen anymore in the vicinity of the Fermi energy.…”
Section: Resultsmentioning
confidence: 51%